Pengaruh Profitabilitas, Ukuran Perusahaan, Dan Jenis Kap Terhadap Pengungkapan Aset Biologis - Usi Gustria; Nurzi Sebrina (Universitas Negeri Padang, 2020)
This study aims to see the effect of profitability, firm size, and type of public accounting firms to biological asset disclosure. The population in this study are all agricultural companies listed on the Indonesia Stock Exchange (IDX) that is as many as 32 companies. The sample in this research use sampling technique purposive sampling counted 13 company in 2016-2018. The analysis was done by using multiple regression model. The results of this study indicate that: (1) The Profitability has no effect on the disclosure of biological asset. (2) Firm size has no effect on biological asset disclosure. (3) type of public accounting firm effect on biological asset disclosure